A Silurian placoderm with osteichthyan-like marginal jaw bones - Zhu, Min; Yu, Xiaobo; Ahlberg, Per Erik; Choo, Brian; Lu, Jing; Qiao, Tuo; Qu, Qingming; Zhao, Wenjin; Jia, Liantao; Blom, Henning; Zhu, You’an (Nature (London), 2013)
The gnathostome (jawed vertebrate) crown group comprises two extant clades with contrasting character complements. Notably, Chondrichthyes (cartilaginous fish) lack the large dermal bones that characterize Osteichthyes (bony fish and tetrapods). The polarities of these differences, and the morphology of the last common ancestor of crown gnathostomes, are the subject of continuing debate. Here we describe a three-dimensionally preserved 419-million-year-old placoderm fish from the Silurian of China that represents the first stem gnathostome with dermal marginal jaw bones (premaxilla, maxilla and dentary), features previously restricted to Osteichthyes. A phylogenetic analysis places the new form near the top of the gnathostome stem group but does not fully resolve its relationships to other placoderms. The analysis also assigns all acanthodians to the chondrichthyan stem group. These results suggest that the last common ancestor of Chondrichthyes and Osteichthyes had a macromeric dermal skeleton, and provide a new framework for studying crown gnathostome divergence. Although the origin of jaws is one of the key episodes in the evolution of vertebrates, the jaw bones of modern bony fishes and limbed vertebrates differ so much from those in any other groups that the individual evolutionary steps in the transition are still unknown; here Entelognathus is described, an early placoderm fish with full body armour, but with marginal jaw bones similar to those of modern bony fishes and limbed vertebrates. The face of vertebrate evolution The development of the jaw is a key episode in vertebrate evolution, but the morphological gap between jawed and jawless vertebrates is so great that it is difficult to identify individual steps involved in the transition. The fossil record can help. Min Zhu and colleagues illuminate a step near the end of the process, in which modern jawed vertebrates such as sharks and bony fish emerge from a collection of jawed, armoured fishes known as placoderms. Most placoderms had jaws very unlike those of modern jawed vertebrates. Enter Entelognathus , a placoderm with full body armour but with jaw bones similar to those of modern bony fish: this the most primitive known creature with what we would recognize as a face.